2020
DOI: 10.1101/2020.09.02.279190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine-scale population structure and demographic history of British Pakistanis

Abstract: Previous genetic and public health research in the Pakistani population has focused on the role of consanguinity in increasing recessive disease risk, but little is known about its recent population history or the effects of endogamy. Here, we investigate fine-scale population structure, history and consanguinity patterns using genetic and questionnaire data from >4,000 British Pakistani individuals, mostly with roots in Azad Kashmir and Punjab. We reveal strong recent population structure driven by the bir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…Ethnicity was self-reported and the homogeneity of the WE group has been confirmed in previous genetic analyses within BIB (33). 93.2% of the included WEs were born in the British Isles (i.e., the UK, Republic of Ireland, Channel Islands or Isle of Man), with the majority in England (91.4%).…”
Section: Methodsmentioning
confidence: 68%
“…Ethnicity was self-reported and the homogeneity of the WE group has been confirmed in previous genetic analyses within BIB (33). 93.2% of the included WEs were born in the British Isles (i.e., the UK, Republic of Ireland, Channel Islands or Isle of Man), with the majority in England (91.4%).…”
Section: Methodsmentioning
confidence: 68%
“…S9b). A notable feature of the XSA cohort is elevated genomic inbreeding, likely due to endogamy 45 , particularly among self-identified Pakistanis 46 (Fig. S9a).…”
Section: Resultsmentioning
confidence: 99%
“…Because we have found that the different types of first-cousin consanguinity generate an observable effect on X chromosomal coalescence times, it is possible that features of coalescence times can be compared across populations to assess signatures of the different types of consanguinity. Such assessments can potentially capitalize on the inverse relationship between coalescence times and genomic sharing (Palamara et al ., 2012; Carmi et al ., 2014; Browning and Browning, 2015) to use genomic sharing patterns to uncover features of consanguinity (Arciero et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%